New ultrasound-assisted microreactor for extracting extraterrestrial biomolecules - Ramzi Timoumi; Rihab Fkiri; Prince Amaniampong; Guillaume Rioland; Brian Gregoire; Pauline Poinot; Claude Geffroy-Rodier (Ultrasonics Sonochemistry)
Searching for organics in extraterrestrial environments, especially biomolecules, continues to be a notable challenge for in situ missions. To address this challenge, this paper introduces an ultrasound (US)-assisted reactor for extraction of amino acids, which complies with space constraints.. The optimal duration for in situ extraction was set at 10 min, using a mixture of water and methanol (1:1, v/v). Compared to 24 h hot water extraction, a 10-min US extraction at 2.4 MHz or 20 kHz enable 80 % of the amino acid recovery from the Mukundpura meteorite and 100 % recovery was achieved when US-assisted extraction was performed three times. Subsequently, the 10-min US extraction at 2.4 MHz was performed in the presence of methyl chloroformate, a derivatisation agent necessary for the gas chromatography–mass spectrometry analysis of amino acids. This simultaneous extraction-derivatisation method, lasting 10 min, enabled the recovery of 80 % of the amino acid content relative to that attainable using the extraction followed by derivatisation method. This simple, rapid, and efficient method enables for the first time the the extraction and detection of amino acids from rock samples. Detection of such biomolecules on planetary or comets surfaces will be a major advance in the understanding of the origins of the first building blocks.